Crystal structure and optimised microwave dielectric properties of Ce2(Zr1-xTix)3(MoO4)9 solid solutions. Issue 4 (15th February 2021) - Zheng, Jinjie; Liu, Yinghao; Tao, Bingjing; Zhang, Qiang; Wu, Haitao; Zhang, Xiaoyu
Abstract: Ce2 (Zr1-x Tix )3 (MoO4 )9 (CZ1-x Tx M) (x = 0.02–0.10) solid solutions were prepared via solid-state reaction method. The effects of Ti 4+ ions substituting for Zr 4+ on sintering behavior, structure and microwave dielectric properties of Ce2 Zr3 (MoO4 )9 ceramics were investigated. X-ray diffraction (XRD) patterns combined with Rietveld refinements results confirmed that all compounds crystallized in a trigonal cell ( R-3c ). The Q·f values of the as-prepared samples were explained by the packing fraction and average grain size. Dielectric polarizability played a significant role in affecting the permittivity, and the τ f values were associated with the bond valence of Zr-site. What's more, far-infrared reflectivity spectra were also used to explore the intrinsic dielectric properties of Ce2 (Zr1-x Tix )3 (MoO4 )9 (x = 0.08) ceramics. Typically, the desirable microwave dielectric properties of Ce2 (Zr1-x Tix )3 (MoO4 )9 ceramics were achieved in x = 0.08 when sintered at 775 °C for 6 h: ε r  = 11.28, Q·f  = 84, 200 GHz and τ f  = −7.86 ppm/°C.